MOTIF POLIGAMI DENGAN WANITA PEKERJA SEKS KOMERSIAL EKS. LOKALISASI MOROSENENG PERSPEKTIF HUKUM ISLAM - Mega Dwi Aprilia (State Islamic University (UIN) of Sunan Ampel, 2017)
This is a field research that focuses on “Polygamy Motive with Commercial Sex Worker Woman in Moroseneng Localization within the Perspective of Islamic Law’. The research aims to find out how Islamic law views polygamy motive with commercial sex worker women in Moroseneng localization, Benowo, Surabaya. If we compare with the polygamy motive under the time of Prophet Muhammad, the polygamy motive with commercial sex worker women in Moroseneng localization is not much different namely to help and elevate women to be more noble. It's just all the motives of polygamy by the Prophet Muhammad’s time are not entirely implemented. The motive of polygamy with commercial sex worker women in Moroseneng localization is more to meet sexual needs and help. However, helping and raising the degree of commercial sex worker women to be a good woman is the main motive. If the polygamy with commercial sex worker women aimed to help, lead, and guide them in goodness and keep them away from evil, give them a lawful living, and can do justice among the wives, then the legal status of polygamy is recommended (sunnah) and allowed